Transformasi Layanan Perpustakaan Condro Utomo Untuk Meningkatkan Literasi Belajar Masyarakat Desa Madyocondro - Lianasari, Dewi; Susmawati, Susmawati; Kurniawan, Dodi; Utaminingsih, Triyuni; Wahyuningrung, Diah Ayu; Darmawan, Reza Rizki (Universitas Nusantara PGRI Kediri, 2022)
This Integrated Community Service Program aims to provide assistance for Condro Utomo library to improve literacy in the community of Madyocondro Village, Secang District, Magelang Regency. Methods are applied in this activity with training and mentoring. The result of this devotional activity is information technology system of library management, arrangement of library materials, bulletins and mading produced by teenagers. This library mentoring activity provides a strong foundation for library management to improve the quality of service to the community, improve literacy and improve the quality of human resources.